2012
DOI: 10.1111/j.1346-8138.2012.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma trough levels of adalimumab and infliximab in terms of clinical efficacy during the treatment of psoriasis

Abstract: We examined the relation between adalimumab and infliximab plasma trough levels, anti-adalimumab and anti-infliximab antibody formation. We analyzed plasma from 32 adalimumab-treated and 20 infliximab-treated psoriasis patients for evaluating trough levels of each drug. The presence of anti-adalimumab and anti-infliximab antibodies was analyzed and the severity of psoriasis was evaluated. At week 28, 25 out of 32 and at week 48, 21 out of 30 adalimumab-treated patients maintained as more than PASI 75. At week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 23 publications
10
84
4
2
Order By: Relevance
“…The average trough level in our patients was 1.90 ug/ml (range 0.40-3.88 ug/ml) and 1.38 (range 0.61-4.04) respectively. It is higher than Takahashi et al [3] published recently in their study of 20 patients treated with infliximab. He found that the minimum trough level of infliximab in good responders was 0.92 ug/ml.…”
Section: Discussioncontrasting
confidence: 53%
“…The average trough level in our patients was 1.90 ug/ml (range 0.40-3.88 ug/ml) and 1.38 (range 0.61-4.04) respectively. It is higher than Takahashi et al [3] published recently in their study of 20 patients treated with infliximab. He found that the minimum trough level of infliximab in good responders was 0.92 ug/ml.…”
Section: Discussioncontrasting
confidence: 53%
“…) and also higher than those reported in other immune-mediated inflammatory diseases [35][36][37]. Consequently, it will be of interest to study whether a lower dose would achieve the same results in patients with active disease.…”
Section: Discussionmentioning
confidence: 69%
“…The discrepancy in study results may suggest that there are other, as yet unexplored, factors with an impact on the efficacy of treatment. Predictors of response autorów uważa, że przyczyna skróconego czasu działania leku może mieć podłoże immunologiczne, takie jak powstawanie przeciwciał przeciwko lekowi [3,21,[30][31][32][33][34][35]. Mogą one hamować jego działanie w terapii długotrwałej lub zmniejszać skuteczność kolejnej zastosowanej terapii biologicznej.…”
Section: Discussionunclassified
“…Wiedza ta umożliwiłaby to biologic therapy have been mentioned to include patient gender [21,24,25,29] and body weight [26]. Many authors claim that a reduced duration of drug action may be attributed to immune factors such as the development of antibodies against the drug [3,21,[30][31][32][33][34][35]. They may inhibit drug action during longterm treatment or reduce the efficacy of the subsequent therapy with biologics.…”
Section: Wnioskimentioning
confidence: 99%